Gravidita a porod u pacientek s implantovaným shuntem pro hydrocefalus - Vybíhal, V; Gerychová, R; Janků, P; Hanoun, G; Sova, M; Fadrus, P; Smrčka, M; Keřkovský, M (Ceska gynekologie, 2014)
UNLABELLED: Hydrocephalus is a disorder of abnormal accumulation of cerebrospinal fluid in the intracranial space, usually in the cerebral ventricles. The number of patients reaching reproductive age and intending to become pregnant has increased in recent years because of treatment advances. An implanted shunt is usually introduced into the abdominal cavity (ventriculoperitoneal shunt). Numerous changes occur during pregnancy, mainly increased accumulation of water, increased intracranial cerebrospinal fluid volume and increased intra-abdominal pressure as a result of the growing uterus. These changes contribute to increased incidence of complications during pregnancy and childbirth. Therefore, it is necessary to make a preconception exam and specify pregnancy management, a suitable method of childbirth and dealing with potential complications. Multidisciplinary care is mandatory with the dominant cooperation of obstetricians and neurosurgeons who should be also available during the delivery when needed. Possible shunt malfunction is necessary to diagnose properly and in time and solve it individually, taking into account the overall and neurological status of the patient and gestational age. The presence of a shunt does not affect pregnancy and vaginal delivery is considered by most authors as the first option. Primary cesarean section is preffered in patients with obstructive hydrocephalus or rapid deterioration in the case of shunt malfunction. Epidural anesthesia or general, eventually spinal anesthesia are recommended. KEYWORDS: hydrocephalus, shunt, ventriculoperitoneal shunt, ventriculoatrial shunt, endoscopy, endoscopic third ventriculostomy, pregnancy.